SURVEY RESEARCH TRAINING FOR VOCATIONAL SCHOOL TEACHERS IN JAKARTA - Prihatni, Rida; Sumiati, Ati; Armeliza, Diah; Khairunnisa, Hera; Nasution, Hafifah (International Journal of Engagement and Empowerment (IJE2), 2024)
This activity is one of the efforts to encourage and empower educators to be more professional and competent. It is intended to make efforts to improve teacher competence in terms of educational and academic professionals and to be able to improve quality continuously. The target audience is teachers of SMKN 10 and SMKN 50. This training provides understanding and knowledge for teachers of SMKN 10 and SMKN 50 in East Jakarta when conducting survey research and writing scientific papers. The results of the training activities went well and smoothly. The teacher's positive appreciation is evidence of this. This appreciation can be seen in the participants' enthusiasm for participating in the activities amid the teachers' busy schedules